Intranasal delivery of a small-molecule ErbB inhibitor promotes recovery from acute and late-stage CNS inflammation - Linnerbauer, Mathias; Lößlein, Lena; Vandrey, Oliver; Tsaktanis, Thanos; Beer, Alexander; Naumann, Ulrike; Panier, Franziska; Beyer, Tobias; Nirschl, Lucy; Kuramatsu, Joji; Winkler, Jürgen; Quintana, Francisco J.; et al. (JCI Insight, 2022)
Multiple sclerosis (MS) is an autoimmune inflammatory disease of the CNS that is characterized by demyelination and axonal degeneration. Although several established treatments reduce relapse burden, effective treatments to halt chronic progression are scarce. Single-cell transcriptomic studies in MS and its animal models have described astrocytes and their spatial and functional heterogeneity as important cellular determinants of chronic disease. We combined CNS single-cell transcriptome data and small-molecule screens in primary mouse and human astrocytes to identify glial interactions, which could be targeted by repurposing FDA-approved small-molecule modulators for the treatment of acute and late-stage CNS inflammation. Using hierarchical in vitro and in vivo validation studies, we demonstrate that among selected pathways, blockade of ErbB by the tyrosine kinase inhibitor afatinib efficiently mitigates proinflammatory astrocyte polarization and promotes tissue-regenerative functions. We found that i.n. delivery of afatinib during acute and late-stage CNS inflammation ameliorates disease severity by reducing monocyte infiltration and axonal degeneration while increasing oligodendrocyte proliferation. We used unbiased screening approaches of astrocyte interactions to identify ErbB signaling and its modulation by afatinib as a potential therapeutic strategy for acute and chronic stages of autoimmune CNS inflammation.
CRIS-Team Scopus Importer:2022-04-22